Performance and Learning Review of the Country Partnership Framework for Kingdom of Cambodia for the Period FY19-FY24 - World Bank; International Development Association; International Finance Corporation; Multilateral Investment Guarantee Agency (World Bank, Washington, DC, 2022)
The Performance and Learning Review (PLR) summarizes progress in the implementation of the World Bank Group (WBG) Country Partnership Framework (CPF) for Cambodia for Fiscal Year (FY) 2019-2023 (Report No. 136500-KH). The CPF, discussed by the Board of Executive Directors on May 30, 2019, proposed a joint WBG program of assistance covering three focus areas: (i) promoting state efficiency and boosting private sector development; (ii) fostering human development; and (iii) improving agriculture and strengthening sustainable use of natural resources. A cross-cutting theme of strengthening governance, institutions and citizen engagement underpins reforms in all three focus areas. These areas address the key development challenges identified in the 2017 Systematic Country Diagnostic (SCD) (Report No. 115189-KH) and are aligned with the Royal Government of Cambodia (RGC)’s Rectangular Strategy Phase IV and the National Strategic Development Plan 2019-2023 and remain relevant to support Cambodia’s post COVID-19 recovery.